Optimisation of simultaneous saccharification and fermentation for biobutanol production using oil palm empty fruit bunch - Md Razali, Nur Atheera Aiza (2018)
Malaysia has a vast amount of tropical agricultural land that suitable for various agricultural activities. A lot of biomass generated from the agricultural activities such as rubber, paddy, fruit and oil palm biomass. Oil palm empty fruit bunch (OPEFB) has been recorded as one of the largest oil palm biomass (18–19 million tonnes/year) produced in palm oil processing mill. OPEFB has the potential as substrate for biobutanol production due to its abundance, cheap and high holocellulose content, thus provide renewability and environmentally friendly biobutanol compared to fossil fuels. Process for biobutanol production from OPEFB can be classified into two major processes: (i) separate saccharification and fermentation (SHF) and (ii) simultaneous saccharification and fermentation (SSF). SSF is a process where the enzymatic saccharification of OPEFB and ABE fermentation are carried out simultaneously in a flask. SSF process has recently gained attention and was proven to be more feasible than SHF, as it reduces the needs for additional equipments therefore lowering in capital, operational costs and time. The main disadvantage of the SSF process is the optimum temperature for fermenting Clostridia (37°C) does not coincide with the optimum temperature for cellulase (50°C). Thus, the objective of this study was to improve the biobutanol production through SSF using OPEFB. The optimisation study consisted of two main parts that employed; one factor at a time (OFAT) approach and using Central Composite Design (CCD) by Response Surface Methodology (RSM). The SSF process successfully produced maximum biobutanol concentration of 1.74 g/L and biobutanol yield of 0.070 g/g at 96 h. The SSF biobutanol yield was comparable to the SHF biobutanol yield of 0.078 g/g. The SSF process was further enhanced by studying the preliminary investigation by OFAT approach. The results generated maximum biobutanol concentration of 2.91g/L and biobutanol yield 0.12 g/g. The percentage of biobutanol increment was 40.21% and 1.71 fold. The biobutanol production was further statistically optimised using CCD. The analysis of variance (ANOVA) showed that the model was very significant (p<0.0010) for the biobutanol production. The optimum fermentation conditions obtained the highest biobutanol production were at temperature of 35°C, initial pH of 5.5, cellulase loading of 15 FPU/g of substrate and 5% (w/v) substrate concentration. From the validation study, the statistical optimisation resulted in a significant increment of biobutanol production of 3.97 g/L with biobutanol yield of 0.16 g/g with 55.95% increment (2.14 fold). The model and optimisation design obtained in this study helps to improve the biobutanol production in which was comparable to other studies of SSF processes using Clostridia species.